Quality of Drinking Water Supply Services in Sidoarjo Regency: Kualitas Pelayanan Penyediaan Air Minum di Kabupaten Sidoarjo - Putri, Desi Diana; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2021)
PDAM Delta Tirta customers expressed complaints that the water does not flow, the water only flows at night, until the water does not flow for several days, and so on. Furthermore, regarding the quantity, the customers complained that the water that came out was small, and for the quality of the water, the customers complained that the water was cloudy yellow to black and smelly. This study aims to describe the quality of drinking water supply services at PDAM Delta Tirta Sidoarjo. The research method used is descriptive qualitative. The data collection techniques obtained are interviews, field observations and documentation. The quality of drinking water supply services at PDAM Delta Tirta Sidoarjo is quite good but needs improvement and improvement in the dimensions of responsiveness. And there are still several obstacles, including the continuity of water flow not being carried out properly, leak sensors are only found in large pipes, cost certainty is disrupted during PSBB during the Covid-19 pandemic, and customer complaints do not receive any follow-up.